â€œShe Had â€˜Ballsâ€™â€: Islamic Liberalism And The Modern Woman In A Contemporary Malaysian Fiction In English - Hosmillo, Bernidick Bryan P. (Bina Nusantara University, 2011)
The paper wants to dissect the plurality of contemporary Malay society by focusing on the constructionÂ of woman sexuality as charged with an amalgam of Islam Parochialism that is seen as a restrictive sociopoliticalÂ mechanism and (de)concentrated modernization that decentres religious functions in contemporaryÂ Malay society and uses instead a rather â€˜filteredâ€™ Islam as colour for the contours of life. Further, the paperÂ underscores the fictive, yet real advances of the Malay woman in terms of critical consciousness and beautyÂ manifested in cultural materialism as both are seriously equated to power. The woman, however, with all theÂ intellectual and material elevation intervenes with (masculine) sexualisation. Hence, the paper capitalizes thenecessity to examine the complexities of masculine sexualisation, as fortified by Western modernity, which is aÂ process of recognizing the feminine presence that inevitably generate erotic desire to sexual fantasy thatÂ ultimately constructs the woman. The paperâ€™s major thrust is to reconceptualise the notion of power anchored inÂ the ideological framework of its polysemous nature. Such progressive elucidation of the concept creates tensionÂ between empowerment and domination which is a relevant concern in feminist politics and interpretations inÂ that the specific implication of such reconceptualization is the Â object of becoming not oppressors, but ofÂ becoming liberated that in the discourse of Malayness is largely problematic as it is always perceived to beÂ antithetical to revitalization of Islam through authentic Malaysian Literature in English for â€˜liberalismâ€™ in thisÂ case, is associated with the rupture of womenâ€™s sexuality.